Interactive LKPD Based on Guided Discovery in Improving Science Learning Outcomes of Grade V Elementary School Students - Suniasih, Ni Wayan; Sujana, I Wayan (LPPM Undiksha, 2023)
This research was carried out on base on phenomena that teachers and students are required to be technologically literate in the learning process along with the development of science and technology which is getting faster in order to be able to compete and increase their potential. Interactive Student Worksheets (LKPD) are needed to guide students in learning to understand the subject matter according to the competencies to be achieved. This study aims to analyze the effectiveness of implementing Guided Discovery-based interactive worksheets on science learning outcomes for fifth grade elementary school students. This experimental research was designed using a non equivalent control group design. The method used to collect research data is in the form of a validated science learning achievement test. The collected data were analyzed using the t-test which was previously tested for normality of data distribution and homogeneity of variance as a prerequisite for analysis. The results showed that there were significant differences in the science learning outcomes of the group of students who were taught with Guided Discovery-based interactive worksheets and the group of students who were taught conventionally. This is evidenced by the results of the tcount test of 6.260 more than the ttable of 2.052. In addition, the results of this study also showed that the results of the Effect Size (ES) test obtained a result of 0.87 in the 0.80 range less than the effective ES in the high effectiveness category. This means that learning using Guided Discovery-based interactive worksheets is effective in improving science learning outcomes for fifth grade elementary school students.